Morfologi Terung (Solanum melongena L.) Pada Berbagai Dosis Biochar Sekam Padi dan Penambahan Pupuk Organik Cair - Tarigan, Tambar Malem; Khairani, Siti; Sembiring, Juhardi (JURNAL AGROPLASMA, 2024)
Eggplant production in Indonesia remains relatively low and has not been able to meet market demands. Long-term use of inorganic fertilizers has led to declining organic matter content in soil, soil degradation, and environmental pollution. To address these issues, agricultural waste such as rice husk can be converted into charcoal or biochar to improve soil quality degraded by excessive use of chemical fertilizers. In addition to biochar as organic material, other organic inputs like liquid organic fertilizer can potentially improve soil physical properties. This research aims to determine the effect of giving rice husk biochar and the correct dose, to find out the effect of applying liquid organic fertilizer and the right concentration and to find out the interaction between giving rice husk biochar and liquid organic fertilizer on eggplant growth and production.The study employs a Randomized Block Design (RBD) factorial with 2 treatment factors. The first factor involves rice husk biochar application at 4 levels (A0: control, A1: 0.6 tons/ha or approximately 30 g/plant, A2: 1.2 tons/ha or approximately 60 g/plant, and A3: 1.8 tons/ha or approximately 90 g/plant). The second factor is liquid organic fertilizer application at 4 levels (B0: control, B1: 0.1 mg/l, B2: 0.3 mg/l, and B3: 0.5 mg/l). The results of the study indicate that rice husk biochar application can increase plant height and leaf number, the best dose for rice husk biochar is 90 g/plant.Application of liquid organic fertilizer has not been able to affect plant height and number of eggplant leaves. Keywords : eggplant, rice husk biochar, liquid organic fertilizer